Kahlil Gibran dan Syairnya tentang Cinta (Kajian Analisis Unsur – Unsur Sastra) - Hikmah, Nur; Hasanuddin, Muh. Iqbal; Hamsa, Hamsa (Al-Syamail: Jurnal Bahasa dan Sastra Arab, 2024)
Poetry is a part of literature that has existed since ancient times. As time progressed, the purpose of poetry became broader and was presented with different themes. There are several periodizations of poetry starting from the jahiliyah period to the modern or current era. Kahlil Gibran is one of the famous poets who lived in modern times. Among Kahlil Gibran's poems that are famous to this day are his poems about love.This research is library research. Library research is research that searches for, collects and analyzes data sources such as books, theses, and so on. The type of data used in this research is descriptive qualitative. Meanwhile, the method used by researchers in collecting data is selecting data related to Kahlil Gibran's poetry, then analyzing and classifying the verses that contain literary elements.Based on research carried out, the author found literary elements contained in Kahlil Gibran's love poetry. The four literary elements are, the emotional element (athifah), the imagination element (khayal), the idea element (fikrah) and the linguistic style element (shurah). In Kahlil Gibran's love poem. With these elements, the love poem can stir emotions among readers and listeners.